Implementation Of Work Safety And Health (K3) Towards Opening Loads At PT. Pelabuhan Indonesia II (Persero) Palembang Branch - Komalasari, Yeti; Sutrisno, Slamet Prasetyo (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
Occupational Safety and Health is very important in a company, especially in construction work. The creation of a sense of security and comfort at work is a demand for companies to be able to fulfill it in order to provide work safety guarantees for project workers and employees. The purpose of this study was to evaluate the process of implementing Occupational Safety and Health (K3) to Unloading Equipment Operators at PT. Pelabuhan Indonesia II (Persero) Palembang branch. The study used survey questions and direct interviews in the field, followed by identification of project locations, visual surveys in the project and documentation taking in the field. K3 implementation in the loading and unloading equipment operator at PT. The Port of Indonesia II Palembang has been running quite well because of the management's efforts to implement K3 rules in accordance with PP No. 50 of 2012, namely the loading and unloading operators are required to use personal protective equipment (PPE) and often carried out socialization about OSH. However, there are still loading and unloading operators who seem not to comply with the rules applied by management and even seem unconcerned with Occupational Safety and Health. The results of the questioner stated, 100% (Yes) because management has implemented K3 regulations namely providing personal protective equipment (PPE) ; 98% know what is meant by Occupational Safety and Health; and 100% of workers claim there is a guarantee of Occupational Safety and Health.